If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2b+5=-2(b+2)+7
We move all terms to the left:
-2b+5-(-2(b+2)+7)=0
We calculate terms in parentheses: -(-2(b+2)+7), so:We get rid of parentheses
-2(b+2)+7
We multiply parentheses
-2b-4+7
We add all the numbers together, and all the variables
-2b+3
Back to the equation:
-(-2b+3)
-2b+2b-3+5=0
We add all the numbers together, and all the variables
2!=0
There is no solution for this equation
| 2x+3x+5=5x+5 | | H+£=y | | -8x+12=-5(8x+4) | | 321321+344.5x=333.64 | | 1/2(3w-8)=25 | | 49=11-2(8+3x) | | 2x16=21-7 | | -81=-41-9n | | 3(x-5)-10=2x-17 | | 3x(5x÷30)×2=7x+60 | | –19j+8j+–4=18 | | 12=17-p | | .7x+.2(40)=0.5(x+20) | | 5y+2+2y+9=12y-9 | | 6(x-9)=6x | | -(x+3)+3x=2(x+3) | | 15x+9=-2x+128 | | x-62=-40 | | -2(2-6n)+6n=9n-4 | | 6=50h-20 | | -r-26=-2(8+3r) | | x-35=17.5 | | 101-x=176 | | 1.2+.5x=4.2 | | 11x-65+25+25=180 | | (1/4)(6x+1)=8 | | 8x=3x×15 | | v/6+10.1=9.1 | | 5p+37=5+2(p+7) | | (4*3)/(2+2)=(16-9)*n/10 | | 3x-8(2x=3)=-6(2x+5) | | -8y-2y=-20 |